IMPLEMENTATION OF THE HEALTH BELIEVE MODEL (HBM) ON COMPLICATION PREVENTION BEHAVIOR IN DIABETIC PATIENTS AT THE PERUMNAS HEALTH COMMUNITY IN REJANG LEBONG REGENCY - Chandra Buana; Derison M Bakara; Tarwoto Tarwoto; Sridiany Sridiany; Rita Harmonis (Poltekkes Kemenkes Bengkulu, 2022)
Diabetes mellitus (DM) is could cause various complications acute metabolic like ketoasiosis and hyperglycemic syndrome which result in syndrome hyperglycemia hyperosmoler nonketotic (HHNK). One of method which used in education health and promotion health is Health Belief Model (HBM) . Research Purpuse; Analyzing the effectiveness of the implementation of the health believe model on complication prevention behavior of DM. Research Design using the method qualitative for knowing perceiver subject to implementation HBM in effort prevention complications disease diabetes mellitus against 7 person subject. Study this carried out in the area of PKM Perumnas Kec. Central Curup, Rejang Lebong District. Data processing and analysis was carried out by To do on going content analysis. Ethics study obtained from commission ethics study Health Polytechnic Ministry of Health Bengkulu no KEPK.M/189/10/2021 date 11 October 2021. Results research ; It was found that although DM is a dangerous disease, it should not be fear and can be controlled with regular treatment and consultation to always maintain health. The obstacles felt by respondents in carrying out routine treatment were the absence of family members who deliver to take medicine to the health center and there is a sense of shame because he always visits the puskesmas to take medicine and the administrative flow is long which must be completed such as taking a referral letter to the hospital. Suggestion; expected to the community to continue to carry out routine treatment and always carry out detection early in prevention complications of DM